2019
DOI: 10.1039/c9ta08107k
|View full text |Cite
|
Sign up to set email alerts
|

Charge transfer modulation in layer-by-layer-assembled multilayered photoanodes for solar water oxidation

Abstract: Two spatially separated charge transfer channels were constructed in multilayered photoanodes for efficient solar water oxidation under both simulated and visible light irradiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 49 publications
2
34
0
Order By: Relevance
“…482 and 493 nm are caused by the bound excitons, and the peaks at 452 and 469 nm result from the band edge free excitons. 25 T(PA) 4 clearly demonstrates the lowest PL density compared to those of its corresponding single-component and binary counterparts, indicating that it has the lowest carrier recombination rate, which is also in agreement with its optimal PEC water oxidation performance. Noteworthily, the PL results of the samples agree well with the PEC water splitting performance results.…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…482 and 493 nm are caused by the bound excitons, and the peaks at 452 and 469 nm result from the band edge free excitons. 25 T(PA) 4 clearly demonstrates the lowest PL density compared to those of its corresponding single-component and binary counterparts, indicating that it has the lowest carrier recombination rate, which is also in agreement with its optimal PEC water oxidation performance. Noteworthily, the PL results of the samples agree well with the PEC water splitting performance results.…”
Section: Resultssupporting
confidence: 68%
“…Layer-by-layer (LbL) assembly utilizes the electrostatic interaction as the driving force to precisely control the integration of building blocks into complex multilayered nanostructures with diverse functionalities. 24–29 In this technique, polyelectrolytes (PEs) with positive or negative ionizable groups are generally utilized to afford charged surfaces on the substrates. 30,31 It was reported that PEs coated on a semiconductor surface are able to foster interfacial charge separation/migration, 32 making them unexpected charge mediators to stimulate photoredox catalysis.…”
Section: Introductionmentioning
confidence: 99%
“…As a homologous counterpart, metal NYs have been regarded as an important category of nanomaterials since they possess a large number of surface active sites and surface plasmon resonance (SPR) effect, making them high-efficiency interfacial charge transfer mediators and light-harvesting antennas. Especially, the plasmonic effect of metal NYs can trigger a coherent electron oscillation under light irradiation, producing an intense electromagnetic field, which leads to a reinforced optical transition in semiconductors along with increased quantum efficiency of photoreactions. Although electrons photoexcited over metal NCs seem a bit like the plasmonic effect of metal NYs in terms of charge transfer from metal to semiconductor for boosting light-harvesting efficiency, a strict and comprehensive comparison of the photoelectrons from metal NCs and hot electrons from plasmonic metal NYs has not yet been reported. This leads us to consider what the intrinsic advantage or disadvantage of photoelectrons from metal NCs compared with hot electrons from metal NYs in affecting interfacial charge transfer efficiency is.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the direct Z‐scheme heterojunction avoids the occurrence of reverse reactions and light shielding phenomena, increases the density of effective photogenerated carriers, and enhances its photocorrosion resistance. The direct Z‐scheme black phosphorus/monolayer Bi 2 WO 6 photoanode prepared by Hu and co‐workers [ 107 ] showed strong photocatalytic performance in H 2 production from water splitting and NO removal for air purification. In Figure 3f, Liu et al [ 108 ] designed and fabricated a black phosphorus/red phosphorus (BP/RP) heterophase junction, and the appropriate band structure with staggered alignment could help to possess the notable separation and transfer capacity of photogenerated electrons and holes.…”
Section: Effective Strategies To Promote Carrier Transport In Photoel...mentioning
confidence: 99%